Reemerging Ebola haemorrhagic fever 2014 and the risks of its introduction into Brazil - Coura, José Rodrigues (2014)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Doenças Parasitárias. Rio de Janeiro, RJ, Brasil.